Variabilidade da precipitação pluvial na UGRH do Médio Paranapanema, Estado de São Paulo - Nery, Jonas Teixeira [UNESP] (2009)
The purpose of this work was to analyze the variability of pluvial precipitation at the Mid-Paranapanema Hydric Resources Management Unit (UGRI II-17), both spatially and temporally. To that effect, 33 pluviometric series were used, obtained from the National Water Agency (ANA), for the period from 1940 to 2000. The averages, standard deviation, upper and lower quartiles, maximum rainfalls, within the analyzed period, as well as the anomalies in these series, were calculated. The anomalies of the 1982/1983 El Nino, as well as the classification of homogeneous areas inside the basin were also calculated. Variability was observed from one year to the other, with rainier years - for example, 1982 and 1983 - and drier years - such as 1985 and 2000.